Vertical gardening: For present age environmental protection - Sahu, K K; Sahu, M (Recent Research in Science and Technology, 2014)
The term “vertical gardening” is self-explanatory. Vertical gardens, also known as green walls are contemporary forms of gardening. The increase in the urban living and lifestyle has raised the number of apartments in India. This has led to the encroachment of spaces all over the city. For a person who is a nature lover, it is very difficult to have their own garden especially when they are residing in an apartment. Perhaps, they need not lose hope as a vertical garden can let you indulge in gardening and your love towards gardening. You can attain this by cultivating a vertical garden in your apartment balconies or any other appropriate place. This will help create green walls in limited space of your apartment. A vertical garden will give your home a chic look by acting as an elegant home décor as well as it freshens up the air. They can be classically minimal or overgrown based on your preference. Vertical gardens can be mounted on walls using different suitable mediums like bags, pouches, water bottles, plastic containers, fabrics and so on. These gardens can be used to block unpleasant sights or penetrating sunlight in your apartment. With the popularity and versatility of vertical gardening systems, there are now several designs of green-walls on the market for both aesthetic and productive gardens. It’s important to have an understanding of the strengths of each system so you can create the effect you are after, not only for the weeks after installation but in the years to come. A vertical garden performs environmental magic while hiding ugly walls or providing the whole family with an abundance of fresh food but they need to be easy to install and even easier to maintain. They add height to horizontal gardens, making them more visually thought provoking.